Clinical Evaluation of Percutaneous Vertebroplasty in a Patient with Paraplegia and Immobilization Syndrome: A Case Report. (14th March 2013) - Masala, Salvatore; Calabria, Eros; Nezzo, Marco; De Vivo, Dominique; Neroni, Luca; Simonetti, Giovanni
Abstract : We will discuss a potential role of percutaneous vertebroplasty (PVP) in the management of a patient with immobilization syndrome due to paraplegia and vertebral osteoporotic fractures. While PVP is commonly used for the treatment of osteoporotic thoracolumbar vertebral compression fractures, its role in vertebral stabilization in patient with immobilization syndrome has not been reported in the literature. A 73-year-old woman affected by immobilization syndrome due to paraplegia and vertebral osteoporotic fractures was treated with PVP of vertebrae D12, L1, and L4. After PVP, the patient did not need any antalgic therapy, and there was a significant improvement regarding mobilization, performance of physiological functions, daily management of personal care, and treatment of decubitus ulcers, increasing life quality and psychological well-being.